(‐)‐Epigallocatechin‐3‐gallate decreases colonic inflammation and permeability in a mouse model of colitis, but reduces macronutrient digestion and exacerbates weight loss. Issue 10 (20th June 2016) - Bitzer, Zachary T.; Elias, Ryan J.; Vijay‐Kumar, Matam; Lambert, Joshua D.
Abstract : (‐)‐Epigallocatechin‐3‐gallate (EGCG) reduces dextran sulfate sodium‐induced colonic inflammation in mice, but reduces macronutrient absorption and exacerbates body weight loss indicating a potential dose‐limiting toxicity. Abstract : Scope: (‐)‐Epigallocatechin‐3‐gallate (EGCG) has been reported to have putative health effects including the prevention of inflammation and obesity. Historically, polyphenols have been regarded as antinutritionals and while such effects may be beneficial in obese subjects, they may be deleterious in nutritionally compromised individuals. Methods and results: We examined the effect of EGCG in the dextran sulfate sodium (DSS)‐treated mouse model of ulcerative colitis. Following induction of colitis, mice were treated with EGCG (3.2 mg/g) as the sole source of drinking fluid for 3 days. EGCG treatment mitigated DSS‐induced colon shortening and spleen enlargement. EGCG also decreased colonic protein levels of IL‐1β, IL‐6, and tumor necrosis factor‐α, as well as colonic lipid peroxides compared to DSS‐treated controls. We observed that EGCG reduced DSS‐induced gastrointestinal permeability. These beneficial effects were offset by enhanced body weight loss in EGCG‐treated mice compared to DSS‐treated controls. These effects were related to decreased protein and lipid digestion in EGCG‐treated mice compared to DSS‐treated controls. Conclusions: Our results suggest that although EGCG may exert anti‐inflammatory effects, its ability to modulate macronutrient digestion may represent a dose‐limiting adverse effect that must be considered in the context of its use for treating inflammatory bowel disease.